Operational Considerations for Urban Economic Inclusion Programming - Dutta, Puja Vasudeva; Clay, Timothy Joseph Peter; Avalos, Jorge Eduardo (Washington, DC: World Bank, 2022)
This note is one of two designed to serve as a resource for policy makers and practitioners aiming to introduce or scale up economic inclusion programs in urban and peri-urban areas. The first note explores the potential of economic inclusion programs to promote the social and economic inclusion of the urban poor and vulnerable. It lays out a framework for such programming based on the current landscape and evidence and points to the central role economic inclusion programs can play in meeting the urban jobs challenge, facilitating a Coronavirus disease 2019 (COVID-19) recovery, and building inclusive cities. This note addresses the question of how to operationalize these programs. It shows that a rethink is needed about the ways in which programs are designed and delivered to fit the needs and lifestyles of the urban poor. The emerging experience from a growing pipeline yields some important operational insights, but several questions remain to be answered in coming years, as programs continue to evolve and customize to the urban context.